Pengaruh Penggunaan Media Audio Visual Dalam Peningkatan Kemampuan Pemahaman Siswa Pada Materi Gerakan Salat Kelas II SDN 12 Kampung Lapai - Intan Prihartini; Alfurqan Alfurqan (Universitas Pahlawan Tuanku Tambusai, 2025)
This research was motivated by differences in understanding and application of learning material by class II students, especially regarding prayer movement material. This results in many students making mistakes in practicing prayer movements, this is because students do not understand and think creatively about the material being taught and the process of delivering the material. boring ri. Therefore, researchers try to use audio visual media in the form of video as communication to convey the material being taught so that the information they want to convey can be received properly. .good by.h students. This research aims to find out the influence of the use of audio-visual media in increasing students' ability to understand the class II prayer movement material at SDN 12 Kampung Lapai.The method used is a quantitative experimental type method. The research sample consisted of 50 people, consisting of 25 people in class II A and 25 people in class II B. The sampling for the two classes used purposive sampling and the population was 50 class II students. The instruments used are tests, data analysis techniques using normality tests, homogeneity tests and T tests. The results of research using T test analysis based on data processing show that the sig value of 0.065 is greater than 0.05 and the calculated t value of 0.939 is smaller than the T table. 1.7655, so Ho is accepted and Ha is rejected, so it can be concluded that there is no influence on the use of audio-visual learning media in increasing students' understanding of prayer material in class II SDN 12 Kampung Lapai.